2023
DOI: 10.3390/ijerph20021373
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Meaningful Places for Aging-in-Place: A Human-Centric Approach toward Inter-Domain Design Criteria Consideration in Taiwan

Abstract: Background: Aging is key to inclusion, and it should be taken into account when designing every place of human activity. However, the implementation of such guidelines often fails the human-centric aspiration as health and design domain interpretation gaps impede the suitable reading and implementation strategies. Purpose: This study aimed to understand critical factors in the place-of-aging and to examine the gap in domain interpretation affecting age-friendly housing. Methods: Using grounded theory as a base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…A recent study revealed that vitamin D supplements prevent nearly 30,000 cancer-related deaths in individuals over 50 years of age, saving a total of 254 million Euros annually in Germany [46]. Taiwan turned into an aged society in 1993 and then an aging society in April 2018, when the number of elderly people increased to 14.10% of the total citizens [47]. Greater attention to older people's health issues is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that vitamin D supplements prevent nearly 30,000 cancer-related deaths in individuals over 50 years of age, saving a total of 254 million Euros annually in Germany [46]. Taiwan turned into an aged society in 1993 and then an aging society in April 2018, when the number of elderly people increased to 14.10% of the total citizens [47]. Greater attention to older people's health issues is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while cognitive-behavioral therapy (CBT) is widely used for younger populations, studies examining its effectiveness for older adults are limited. Research demonstrates that older adults often present with different symptoms of depression, such as increased irritability or cognitive decline, yet interventions frequently do not account for these unique factors [ 5 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%